Evaluation of a new wideband slot array for MIMO performance enhancement in indoor WLANs - Costa, Jorge R. (2014)
A new wideband compact slot antenna array for indoor WLAN access points (AP) is described, covering several wireless communication services from 2.4 to 4.8 GHz, that is especially designed to enhance MIMO system capacity. The array topology provides both spatial and polarization diversity. Despite very close packing of the array elements, these exhibit very low mutual coupling and low cross-polarization, greatly favoring MIMO diversity gain. A detailed MIMO performance comparison is conducted against a common array of patches in indoor environment, based both on simulation and indoor measurements: the new antenna shows a clear improvement in terms of channel capacity.